Analisis Kualitas Pelayanan Publik Dan Gaya Kepemimpinan Kepala Desa (Studi Pada Bidang Pelayanan Kependudukan Di Kantor Desa Semen Kabupaten Kediri) - Curtinawati, Rizki Fillya (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
The importance of ensuring the availability and quality of public services provided by the Government has a very significant impact. because it is synchronized with its objectives, excellent service quality is an effort to provide services that can meet and satisfy the community and convey the focus of service to the people... The scope of services of the Semen Village Government, Pagu Sub-district, Kediri District, is related to public services such as population services, namely the services of Identity Cards (KTP) and Family Cards (KK). However, based on initial researcher observations and the results of interviews with several residents that are still not maximized in terms of timeliness, financing procedures and the level of document printing errors. Thus, it means that the quality of public services in the village office of Semen Village, Pagu District, Kediri Regency is still not very effective, meaning that it is still very necessary to improve the quality of these services. This research uses descriptive with a qualitative approach. The focus of this research on the quality of public services and the leadership style of the Semen Village Office. The result is that the quality of service at the Semen Village Office, Pagu District, Kediri Regency is less qualified. This is based on the results of research from 4 dimensions, there are 2 dimensions that are less than optimal, namely Physical Evidence and Reliability, while the others are already running well. In addition, the leadership style used by the Village Head is an autocratic leadership style so that it has an impact on service quality.